Overcoming Cyberbullying with Empathy: The ‘Weirdos’ Film Shows How Patience and Strong Character Matters - Indrani Dewi Anggraini; Nani Nuraini Sarah (Scope : Journal of English Language Teaching, 2023)
Bullying seriously violates the ethics of human relations. It is a serious problem that affects the mental health of young people, and sadly at times, it can even result in the tragic death of the victims. The act of bullying in the form of gossiping, mocking, laughing at them, or even "seemingly harmless" physical acts, is often not taken seriously and is even interpreted as an act of joking. These acts are often felt by victims as deeply disturbing as they suffer from physical pain and mental anguish due to body shame as is seen in the film “Weirdos”. This study aims to describe, to analyze, and to interpret critically the film based on the aspects of the victim's character-building through traits that range from empathy, passion, and  patience to stop the tyranny of bullying. Using the descriptive and qualitative method with an eclectic approach and content analysis, the data of this study were selected from film’s sceneries  The results of this study show that being empathy namely patience and passion, bullying can be overcome.  Apart from this, these positive traits might lead to a greater awareness of how certain virtues of victims and their strength of character can overcome bullying. Finally, this study promotes film as a means of educational media to spread awareness of the impacts of bullying.